Non-Palladium-Catalyzed Oxidative Coupling Reactions Using Hypervalent Iodine Reagents - Shetgaonkar, Samata E.; Raju, Aleena; China, Hideyasu; Takenaga, Naoko; Dohi, Toshifumi; Singh, Fateh V. (Frontiers in Chemistry, 2022)
Graphical Abstract